Transcription factor AP2 controls cnidarian germ cell induction - DuBuc, Timothy Q.; Schnitzler, Christine E.; Chrysostomou, Eleni; McMahon, Emma T.; Febrimarsa; Gahan, James M.; Buggie, Tara; Gornik, Sebastian G.; Hanley, Shirley; Barreira, Sofia N.; Gonzalez, Paul; Baxevanis, Andreas D.; et al. (Science, 2020)
Conserved gene specifies germ cell - Germ cells are the exclusive progenitors of gametes. In most studied animals, including humans, germ cells are produced only once during embryogenesis and are not replenished in adult life. DuBuc et al. studied germ cell induction in the clonal cnidarian Hydractinia symbiolongicarpus, an animal that forms germ cells continuously in adult life from stem cells that also generate somatic cells. A single transcription factor is capable of converting the animal's adult stem cells to germ cells. A similar gene also controls germ cell induction in mammalian embryos, but its action there is limited to a single event in early embryogenesis. - Science, this issue p. 757 - Clonal animals do not sequester a germ line during embryogenesis. Instead, they have adult stem cells that contribute to somatic tissues or gametes. How germ fate is induced in these animals, and whether this process is related to bilaterian embryonic germline induction, is unknown. We show that transcription factor AP2 (Tfap2), a regulator of mammalian germ lines, acts to commit adult stem cells, known as i-cells, to the germ cell fate in the clonal cnidarian Hydractinia symbiolongicarpus. Tfap2 mutants lacked germ cells and gonads. Transplanted wild-type cells rescued gonad development but not germ cell induction in Tfap2 mutants. Forced expression of Tfap2 in i-cells converted them to germ cells. Therefore, Tfap2 is a regulator of germ cell commitment across germ line-sequestering and germ line-nonsequestering animals. - A single transcription factor commits adult stem cells to germ cell fate and induces gonad development in Hydractinia symbiolongicarpus. - A single transcription factor commits adult stem cells to germ cell fate and induces gonad development in Hydractinia symbiolongicarpus.